2014
DOI: 10.1016/j.aop.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

General N=2 supersymmetric quantum mechanical model: Supervariable approach to its off-shell nilpotent symmetries

Abstract: h i g h l i g h t s• A novel method has been proposed for the derivation of N = 2 SUSY transformations. • General N = 2 SUSY quantum mechanical (QM) model with a general superpotential, is considered. • The above SUSY QM model is generalized onto a (1, 2)-dimensional supermanifold.• SUSY invariant restrictions are imposed on the (anti-)chiral supervariables. • Geometrical meaning of the nilpotency property is provided.Nilpotency property a b s t r a c t Using the supersymmetric (SUSY) invariant restrictions on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…We envisage to take up these challenges in our future investigations. Before we end this section, it is worthwhile to point out that in our earlier works (see, e.g., [27,28]), we have applied the techniques and tricks of ACSA to obtain the nilpotent symmetries of the N = 2 SUSY quantum mechanical models of interest. However, we have found that the conserved charges are not absolutely anticommuting.…”
Section: Discussionmentioning
confidence: 99%
“…We envisage to take up these challenges in our future investigations. Before we end this section, it is worthwhile to point out that in our earlier works (see, e.g., [27,28]), we have applied the techniques and tricks of ACSA to obtain the nilpotent symmetries of the N = 2 SUSY quantum mechanical models of interest. However, we have found that the conserved charges are not absolutely anticommuting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have shown that the perfect analogy between the de Rham cohomological operators of differential geometry and the N = 4 SUSY transformations (and their conserved Noether charges and Hamiltonian of the system) exists at the algebraic level, in our present investigation. In our present endeavor, we have applied supervariable approach (we have already applied this approach for different N = 2 SUSY QMMs in [15][16][17]23,24]) for the derivation of the SUSY transformations for the N = 4 SUSY QMM of a charged particle (i.e. an electron) moving on a sphere in the background of Dirac magnetic monoploe [26] within the framework of (anti-)chiral super-submanifolds.…”
Section: Discussionmentioning
confidence: 99%
“…In the above, one set of discrete symmetry transformations endow parity symmetry and the other does not, along with the time-reversal symmetry. Now, from the discrete symmetries listed in (7), concentrating on the all upper signatures only (i.e.…”
Section: Pos(ichep2020)664mentioning
confidence: 99%